2019
DOI: 10.1590/1414-431x20199124
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 125 predicts pulmonary congestion in patients with ST-segment elevation myocardial infarction

Abstract: Carbohydrate antigen 125 (CA125) has long been used as an ovarian cancer biomarker. However, because it is not specific for ovarian cells, CA125 could also be used to monitor congestion and inflammation in heart disease. Acute heart failure (HF) is used to identify patients with a worse prognosis in ST-segment elevation myocardial infarction (STEMI). We aimed to determine the association of CA125 with acute HF in STEMI and to compare CA125 with N-terminal pro brain natriuretic peptide (NTproBNP) with a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Plasma levels of CA125 are higher in patients with peripheral and/or pulmonary oedema and are further elevated in patients with serosal effusion compared with patients with acute heart failure without pronounced serosal effusion 78,79 . In patients with myocardial infarction, increased plasma levels of CA125 predict the onset of heart failure 80 . The CHANCE HF study 81 examined the use of CA125 guided therapy versus standard of care in patients with acute heart failure and found a lower rate of rehospitalization for acute decompensated heart fail ure in the CA125 guided group.…”
Section: Carbohydrate Antigen 125mentioning
confidence: 99%
“…Plasma levels of CA125 are higher in patients with peripheral and/or pulmonary oedema and are further elevated in patients with serosal effusion compared with patients with acute heart failure without pronounced serosal effusion 78,79 . In patients with myocardial infarction, increased plasma levels of CA125 predict the onset of heart failure 80 . The CHANCE HF study 81 examined the use of CA125 guided therapy versus standard of care in patients with acute heart failure and found a lower rate of rehospitalization for acute decompensated heart fail ure in the CA125 guided group.…”
Section: Carbohydrate Antigen 125mentioning
confidence: 99%
“…[ 43 , 44 ] Similarly, in patients with ST-elevation MI (STEMI) complicated with HF (Killip Class ≥II), circulating CA125 concentrations were correlated with pulmonary congestion and had similar prognostic power for mortality as high-sensitivity C-reactive protein and N-terminal pro B-type natriuretic peptide (NT-proBNP) in the STEMI population. [ 45 , 46 ] In line with this, CA125 was shown to be associated with well-established laboratory proxies of clinical congestion, such as bio-adrenomedullin and NT-proBNP. [ 47 ] In fact, one study showed that in clinical scenarios marked by systemic congestion and right ventricular dysfunction, CA125 may even outperform NT-proBNP in predicting mortality.…”
Section: Ca125 As An Indicator Of Congestion In Heart Failure and Its Relationship With Haemodynamic And Echocardiographic Parametersmentioning
confidence: 77%
“…Although CA-125 and natriuretic peptides have different pathophysiological mechanisms and half-lives (BNP ∼ 20-30 minutes), significant correlations have been identified between them in the presence of heart failure. Moreover, strong associations of CA-125 with inflammatory stimuli, echocardiographic and hemodynamic parameters, mortality or re-hospitalization risk of patients during follow-up have been reported [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [25] , [26] , [27] , [28] , [29] , [31] , [37] , [39] , [45] . An improvement in LVEF with a marked decrease in CA 125 levels after treatment in heart failure patients, the observation of reductions in pericardial effusion, and also the ability to monitor treatments that affect cytokine levels through CA-125 levels make it a valuable marker [4] , [10] , [17] , [19] , [21] , [25] , [26] , [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the literature supporting this hypothesis demonstrating the clinical usefulness of CA-125 are: (I) Positive correlations were reported between serum CA- 125 levels and CRP/hs-CRP, BNP/NT-proBNP, cytokines (TNF-α, IL-1, IL-6, IL-10) [17] , [18] , [19] , [25] , [30] , [37] , [38] , [39] ; (II) Elevated CA-125 levels were associated with the severity of diastolic and systolic dysfunctions in many studies supplemented by echocardiographic data. Positive and significant correlations also were found with left ventricular ejection fraction (LVEF), systolic pulmonary artery pressure (SPAP), right atrial pressure, pulmonary artery wedge pressure, left atrial volumes [15] , [16] , [17] , [18] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [30] , [31] , [37] , [39] ; (III) A positive correlation was detected between CA-125 and ventricular remodeling. Thus, It was suggested that high serum CA-125 levels in coronary heart patients may help predict the risk of short-term heart failure and death [24] ; (IV) It was reported that patients with increased CA-125 levels have a higher risk of developing atrial fibrillation [15] , [17] , [18] , [27] ; (V) Elevated CA-125 levels were also observed in other cardiac pathologies such as tricuspid stenosis, mitral stenosis, mitral valve endocarditis, atrial septal defect, pulmonary hypertension, aortic stenosis, and acute coronary syndromes [25] , [27] , [37] ; (VI) There is evidence that changes in serum CA-125 levels as a result of the therapy protocol used heal the clinical course [37] .…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
See 1 more Smart Citation